2021
DOI: 10.3390/jcm10061330
|View full text |Cite
|
Sign up to set email alerts
|

Progression in the Management of Non-Idiopathic Pulmonary Fibrosis Interstitial Lung Diseases, Where Are We Now and Where We Would Like to Be

Abstract: A significant proportion of patients with interstitial lung disease (ILD) may develop a progressive fibrosing phenotype characterized by worsening of symptoms and pulmonary function, progressive fibrosis on chest computed tomography and increased mortality. The clinical course in these patients mimics the relentless progressiveness of idiopathic pulmonary fibrosis (IPF). Common pathophysiological mechanisms such as a shared genetic susceptibility and a common downstream pathway—self-sustaining fibroproliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 109 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…The results of the INBUILD study showed that anti-fibrotic therapy with nintedanib slowed the rate of FVC loss in a population of patients who developed progressive fibrosis (PF-ILD) in interstitial diseases other than IPF (non-IPF ILD) [ 16 ]. Moreover, an additional post hoc analysis of the study’s results in the overall patient population that evaluated the predicted categorical absolute changes in FVC percentage (FVC%) over a 52-week study period showed that the percentage of patients experiencing clinically meaningful declines in FVC% (FVC decline ≥5%) was lower in the nintedanib group compared with that in the placebo group [ 107 , 108 ]. Currently, there are no data on the efficacy of nintedanib in patients with PF-ILDs beyond 52 weeks or data indicating the benefit of continuing anti-fibrotic treatment in patients with PF-ILDs who experience disease progression during such treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the INBUILD study showed that anti-fibrotic therapy with nintedanib slowed the rate of FVC loss in a population of patients who developed progressive fibrosis (PF-ILD) in interstitial diseases other than IPF (non-IPF ILD) [ 16 ]. Moreover, an additional post hoc analysis of the study’s results in the overall patient population that evaluated the predicted categorical absolute changes in FVC percentage (FVC%) over a 52-week study period showed that the percentage of patients experiencing clinically meaningful declines in FVC% (FVC decline ≥5%) was lower in the nintedanib group compared with that in the placebo group [ 107 , 108 ]. Currently, there are no data on the efficacy of nintedanib in patients with PF-ILDs beyond 52 weeks or data indicating the benefit of continuing anti-fibrotic treatment in patients with PF-ILDs who experience disease progression during such treatments.…”
Section: Resultsmentioning
confidence: 99%
“…There are fewer effective drugs for the treatment of IPF in the clinic, so although the incidence of the disease is low, the prognosis is extremely poor [ 22 , 23 ]. Several studies [ 24 26 ] have proved that pirfenidone has anti-fibrosis, anti-oxidation and anti-inflammatory effects. It mainly inhibits transforming growth factor (TGF)-β, tumor necrosis factor (TNF)-α and platelet-derived growth factor (PDGF) to produce an anti-fibrosis effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, data on therapy are not provided. However, the effect of available antifibrotic medication on pulmonary function and cardiopulmonary exercise capacity is undisputable [ 8 , 62 , 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%